Fluid and thermal behaviour of multi-phase flow through curved ducts - Nadim, Nima (Curtin University, 2012)
Fluid flow through curved ducts is influenced by the centrifugal action arising from duct curvature and has behaviour uniquely different to fluid flow through straight ducts. In such flows, centrifugal forces induce secondary flow vortices and produce spiralling fluid motion within curved ducts. Secondary flow promotes fluid mixing with intrinsic potential for thermal enhancement and, exhibits possibility of fluid instability and additional secondary vortices under certain flow conditions. Reviewing published numerical and experimental work, this thesis discusses the current knowledge-base on secondary flow in curved ducts and, identifies the deficiencies in analyses and fundamental understanding. It then presents an extensive research study capturing advanced aspects of secondary flow behaviour in single and two-phase fluid flow through curved channels of several practical geometries and the associated wall heat transfer processes.As a key contribution to the field and overcoming current limitations, this research study develops a new three-dimensional numerical model for single-phase fluid flow in curved ducts incorporating vortex structure (helicity) approach and a curvilinear mesh system. The model is validated against the published data to ascertain modelling accuracy. Considering rectangular, elliptical and circular ducts, the flow patterns and thermal characteristics are obtained for a range of duct aspect ratios, flow rates and wall heat fluxes. Results are analysed for parametric influences and construed for clearer physical understanding of the flow mechanics involved. The study formulates two analytical techniques whereby secondary vortex detection is integrated into the computational process with unprecedented accuracy and reliability. The vortex inception at flow instability is carefully examined with respect to the duct aspect ratio, duct geometry and flow rate. An entropy-based thermal optimisation technique is developed for fluid flow through curved ducts.Extending the single-phase model, novel simulations are developed to investigate the multiphase flow in heated curved ducts. The variants of these models are separately formulated to examine the immiscible fluid mixture flow and the two-phase flow boiling situations in heated curved ducts. These advanced curved duct flow simulation models are validated against the available data. Along with physical interpretations, the predicted results are used to appraise the parametric influences on phase and void fraction distribution, unique flow features and thermal characteristics. A channel flow optimisation method based on thermal and viscous fluid irreversibilities is proposed and tested with a view to develop a practical design tool.